The use of kaolin for passive sampling of volatile organic compounds in air - St í¶nner, Christof; Mateu, Daniel; De la Guardia, Miguel (Ciencia, 2015)
The use of kaolin as adsorbent to fill semipermeable membrane devices (SPMDs) in order Â Â to catch volatile organic compounds (VOCs) from air has been evaluated. The quantification was Â Â performed by head-space sampling-gas chromatography (HS-GC-MS) using a multi-analyte calibration in spiked passive samplers in a range of 15 ng to 15 Âµg and providing a multi-residue analytical procedure. The omission of sample pre-treatment and the avoidance of deleterious solvents make possible a fast, direct and green determination of VOCs in air with limit of detection values of the order of 40ng per sampler.Â